Localized ulcerative nodular amyloidosis presenting as ulcerative panniculitis, an unusual clinical manifestation: A case report. (November 2019) - Fernandes, Carolina; Éthier, Vincent; Marouan, Sofia; Chababi-Atallah, Myrna; Veilleux, Mylène
Introduction and objectives: The main objective of this article is to present and discuss a case of localized ulcerative nodular amyloidosis with deep involvement clinically manifesting as ulcerative panniculitis and discuss its impact on the choice of treatment. Methods and results: We present a 73-year-old woman with a history of painful ulcerated nodules on the inferior limbs. Microscopy confirmed amyloid deposits deep in the dermis and subcutaneous fat. No systemic involvement was found. Considering that skin-directed treatments often are not able to reach subcutaneous fat or were contraindicated because of the ulcers, she was successfully treated with cyclophosphamide and prednisone. Conclusion: Localized ulcerative nodular amyloidosis with deep involvement is a rare clinical presentation that can present as ulcerative panniculitis. Such a clinical manifestation might be misleading. Systemic treatment might be necessary to control symptoms when conventional skin-directed therapies are contraindicated.